CCD photometric study of the contact binary TX Cnc in the young open cluster NGC 2632 - Liang Liu (2018)
TX Cnc is a member of the young open cluster NGC 2632. In the present paper, four CCD epochs of light minimum and a complete V light curve of TX Cnc are presented. A period investigation based on all available photoelectric or CCD data showed that it is superimposed on a long-term increase (dP/dt = +3.97 × 10-8d yr-1), and weak evidence suggests that it includes a small-amplitude period oscillation (A3= 0.d0028; T3= 26.6 yr). The light curves in the V band obtained in 2004 were analyzed with the 2003 version of the W-D code. It was shown that TX Cnc is an overcontact binary system with a degree of contact factor f = 24.8% (±0.9%). The absolute parameters of the system were calculated: M1= 1.319 ±0.007M⊙, M2= 0.600 ± 0.01 M⊙; R1= 1.28 ± 0.19R⊙, R2= 0.91 ± 0.13R⊙. TX Cnc may be on the TRO-controlled stage of the evolutionary scheme proposed by Qian (2001a, b, 2003a), and may contain an invisible tertiary component (m3≈ 0.097M⊙). If this is true, the tertiary component has played an important role in the formation and evolution of TX Cnc by removing angular momentum from the central system (Pribulla & Rucinski 2006). In this way the contact binary configuration can be formed in the shortlife time of a young open cluster via AML. © 2007. Astronomical Society of Japan.